2017
DOI: 10.1002/jcad.12132
|View full text |Cite
|
Sign up to set email alerts
|

A National Survey on Multicultural Competence for Professional Counselors: A Replication Study

Abstract: The purpose of this investigation was to replicate findings from Holcomb‐McCoy and Myers's () study, which assessed the multicultural competence of professional counselors. Factor analysis was conducted to determine the components of multicultural competence (N = 171). Differences existed between multicultural competence and race/ethnicity, F(2, 168) = 4.86, p = .009, Wilks's Λ = .95, partial η2 = .06, and education level, F(2, 167) = 8.95, p < .001, Wilks's Λ = .82, partial η2 = .10.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
34
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 33 publications
(39 citation statements)
references
References 34 publications
4
34
1
Order By: Relevance
“…Holcomb- McCoy and Myers (1999) found no statistical difference on self-reported measures of multicultural competence between CACREP and non-CACREP training. Barden, Sherrell, and Matthews (2017) replicated Holcomb-McCoy and Myers's study and found the same results. Holcomb-McCoy and Myers's survey focused on the race/ethnicity denomination of multicultural competency.…”
Section: Factors Influencing Multicultural Competencysupporting
confidence: 78%
See 4 more Smart Citations
“…Holcomb- McCoy and Myers (1999) found no statistical difference on self-reported measures of multicultural competence between CACREP and non-CACREP training. Barden, Sherrell, and Matthews (2017) replicated Holcomb-McCoy and Myers's study and found the same results. Holcomb-McCoy and Myers's survey focused on the race/ethnicity denomination of multicultural competency.…”
Section: Factors Influencing Multicultural Competencysupporting
confidence: 78%
“…Barden et al () and Holcomb‐McCoy and Myers () found no significant differences between CACREP and non‐CACREP programs. Our study found that SCTs from non‐CACREP school counselor training programs reported higher perceived multicultural competency and training of social class and classism than SCTs from CACREP programs.…”
Section: Discussionmentioning
confidence: 94%
See 3 more Smart Citations